Prevalence and Risk Factors of Elderly Abuse in Family Environment - Timalsina, Keshab Prasad; Baral, Rameshor; Timalsina, Bhim Prasad; Dhungel, Basu Prasad; Chaulagain, Anju (International Research Journal of MMC, 2023)
Elder abuse in the family is a widespread and challenging issue in society. The purpose of this study is to look into the prevalence of elderly abuse in the family environment of Hetauda Sub-Metropolitan City, as well as the risk factors that influence it. A survey of 412 elders was conducted using simple random sampling. The data was gathered using a structured face-to-face interview schedule. Descriptive and binary logistic regression analysis was used to analyses the collected data. The descriptive and inferential analysis of the collected data demonstrated that elderly abuse occurred in 35.90% of the study population. Elders with functional disability had the highest odds ratio (binary logistic regression) of being abused (12.13 times), followed by living without a spouse (4.44 times), elders without property ownership (3.84 times), and illiteracy (3.06 times), according to the study. Although the prevalence in this study was lower than in many previous studies, the prevalence of 35.90 percent is still significantly high and should be avoided. The study discovered a significant use of social exchange theory and Foucault's view on power in describing Nepalese social behavior. Having a functional disability, living without a spouse, not owning property, and being illiterate are the major predictors of elderly abuse, according to the study. The study emphasizes the importance of policies and programmes aimed at preventing elder abuse, which undoubtedly necessitates collaboration between the social, health, and justice sectors. In Nepalese society, functional disability, living without a spouse, not owning property, and being illiterate are major predictors of elder abuse. To prevent elder abuse, policies and programmes are required, as well as collaborative action from the social, health, and justice sectors.